2023
DOI: 10.1212/wnl.0000000000201346
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Behavioral, Biological, and Genetic Markers of Cardiovascular Health and MRI Markers of Brain Aging

Abstract: Background and Objective:The Life’s Simple 7 approach was proposed to define cardiovascular health (CVH) metrics. We sought to investigate the associations between behavioral, biological, and genetic markers for CVH and vascular brain aging in older adults.Methods:This population-based cohort study included participants who had repeated brain MRI measures from 2001-2003 to 2007-2010 (i.e., count of perivascular spaces, volumes of white-matter hyperintensity [WMH] and grey matter, and lacunes). At baseline, glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…One view is that a higher BDA is an indicator of accelerated brain aging that has accumulated over an individual's lifetime [35]; another postulates that individuals vary in their brain and body health from the beginning of life [36,37]. Both perspectives are supported by the results of empirical studies; perinatal variables (birth weight) and genetic variability are associated with BDA [36,38] Vascular risk factors may be reflected in features seen on brain MRI, for example global white matter hyperintensities [42,43], which may not be fully captured by the DNN algorithm of BDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One view is that a higher BDA is an indicator of accelerated brain aging that has accumulated over an individual's lifetime [35]; another postulates that individuals vary in their brain and body health from the beginning of life [36,37]. Both perspectives are supported by the results of empirical studies; perinatal variables (birth weight) and genetic variability are associated with BDA [36,38] Vascular risk factors may be reflected in features seen on brain MRI, for example global white matter hyperintensities [42,43], which may not be fully captured by the DNN algorithm of BDA.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that vascular dysfunction is not necessarily reflected in morphological structures of the brain, at least not at the time point when the measurements of HDA and BDA were conducted in our population‐based sample. Vascular risk factors may be reflected in features seen on brain MRI, for example global white matter hyperintensities [42, 43], which may not be fully captured by the DNN algorithm of BDA.…”
Section: Discussionmentioning
confidence: 99%
“…Poor CVH has previously been related to greater white matter hyperintensity volume, silent brain infarcts, lower gray matter perfusion, and lower brain volume, which may mediate the association between CVH and cognitive function [29, 30]. In addition, a recent study showed that LS7 was related to levels of cerebrospinal Alzheimer's disease biomarkers, suggesting a link between better CVH and a lower degree of Alzheimer's disease pathology [31].…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental impact of even subtle cardiovascular risk factors has also been hypothesized to be more prominent among individuals who carry at least one e4 allele [ 115 ]. In this context, the potential interaction between MBI and PRSs in terms of predisposition to cardiovascular risk factors, such as diabetes, hyperlipidemia, or hypertension, that have been associated with white matter hyperintensities [ 116 ] should be also investigated.…”
Section: Future Perspectivesmentioning
confidence: 99%